Administrative Responsibility in the Field of Road Safety: Current Trends and Prospects - V. I. Maiorov; O. I. Beketov (Сибирское юридическое обозрение)
The article discusses the prospects and current trends of administrative responsibility in the field of road safety. The priorities of the state policy in the field of road safety are defined in the Strategy of road safety in the Russian Federation for 2018-2024, which, among other things, notes the need to improve legal liability for offenses in this area. Based on the analysis of a number of initiatives put forward to date by the subjects of lawmaking to strengthen administrative responsibility for offenses in the field of traffic, it can be argued that their essence is to constantly increase sanctions and the introduction of new compositions of offenses against drivers of vehicles. At the same time, other road users, as well as legal entities whose activities have an impact on road safety, are not a priority object of impact, largely due to the high latency of their offenses. Based on the analysis and arguments, the following conclusions: 1) the most effective way of differentiation and individualization of administrative responsibility of drivers of vehicles; 2) it is necessary to improve the mechanisms of detection and suppression of administrative offenses in the field of road safety committed by legal entities, as well as certain categories of road users (pedestrians, passengers).